KARTELE EKSPORTOWE W ŚWIETLE PRAWA OCHRONY KONKURENCJI - Molski, Rajmund (Wydział Prawa i Administracji UAM, 2003)
The term export cartels denotes agreements between companies operating in the same industry which aim at restricting (or even eliminating) mutual competition in export of the goods (or services) offered on one or more foreign markets. Such dealings are coordinated between independent companies and replace their unconstrained decisions on export of goods or services to foreign markets with an arrangements on prices, production volume or other business parameters. Not all cooperation agreements between exporters can be deemed to involve export cartel definition. Furthermore, not all export cartels are detrimental per se or even from the standpoint of importing country. Increased productivity and competition-friendly impact on the export in the source country may also prove beneficial for the consumers of the importing country. This is notably true of the cartels of innovative character that aim at research and development cooperation (R&D cartels). However some forms of cartelizing, both domestic and exporting, bring about particularly negative consequences for the operation of markets (the so-called „hardcore cartels”). The paper examines different forms of the various cartels, presents their typology and analyzes their activities worldwide, providing examples of their operations on the world market. It also explains the rationale behind their establishment and consequences of their operation from the standpoint of competition regulations.
EXPORT CARTELS IN THE LIGHT OF COMPETITION LAW